Assessment of Demand and Supply of Biotechnology of Reproduction for Cattle Breeding in the Northern Regions of Cameroon - Justin Kouamo; Paul Pa-ana; Andre Pagnah Zoli (Journal of Livestock Science and Production, 2019)
The present study was conducted in pre-selected cattle farms on genetic improvement programs through artificial insemination (AI) in the northern regions of Cameroon. The main objective was to assess the demand and supply of biotechnology for cattle breeding. It was carried out on the basis of a survey of 54 breeders and six (06) service providers of reproductive biotechnologies. It consisted of interviews with each operating manager and service provider, while collecting information on the basis of a questionnaire. From this study, it appears that farmers opted for the improvement of dairy genes (79.6%) and chose AI (50%) as a tool to achieve this goal rather than natural mating (48.1%). The low success rate and the prohibitive cost of this technique were the main constraints discouraging farmers from adopting it. The subvention and the zoo-sanitary follow-up were the accompanying measures desired by the breeders. As for the supply, AI on induced estrus was the only technique offered and only one provider (veterinary doctor) has been trained in a specialized institution. The main constraints identified by reproductive biotechnology service providers were semen conservation (100%), breeders’ neglect (100%) and unavailability of semen (50%). Four support measures were desired by the service providers, namely a training center in biotechnology of reproduction (100%), grants (83.3%), establishment of a quality control laboratory for semen (50%) and the creation of a semen collection center (33.3%).